Unique features of non-IgE-mediated gastrointestinal food allergy during infancy in Japan. Issue 3 (June 2020) - Yamada, Yoshiyuki
Abstract : Purpose of review: An increase in incidence of unique phenotypic non-IgE-mediated gastrointestinal food allergies (non-IgE GIFAs) has occurred in Japan ahead of Western countries. There are differences in clinical features of non-IgE GIFAs in Western and Japanese patients. As this phenotype has now come to be recognized internationally, we describe it in this review. Recent findings: A large number of Japanese patients with non-IgE GIFAs present with vomiting accompanied by bloody stool, putting them between food protein-induced enterocolitis syndrome (FPIES) and food protein-induced allergic proctocolitis. Some neonates and early infants with non-IgE GIFAs who present with fever and elevated C-reactive protein have symptoms consistent with severe systemic bacterial infections (e.g., sepsis). Some of these cases have now been defined in international guidelines as chronic FPIES. Eosinophils might be involved in the inflammatory process observed. The incidence of FPIES and food protein-induced allergic proctocolitis is increasing in Western countries and likely worldwide, after it has increased in Japan. Summary: The phenotype observed in Japan shows distinct clinical features compared with the classical phenotype, that is, increased levels of eosinophils, suggestive of 'eosinophilic shift' alongside symptomatic differences, making it difficult to categorize.